ChemInform Abstract: A New Phase in the MnII—SeIV—MoVI—O System, Mn(MoO3)(SeO3)(H2O): Hydrothermal Synthesis, Crystal Structure and Properties. Issue 5 (4th February 2014) - Zhen, Yanzhong; Wang, Danjun; Liu, Bin; Fu, Feng; Xue, Ganglin
Abstract The title compound is hydrothermally synthesized from an aqueous mixture of Na2MoO4, SeO2, and MnSO4 (autoclave, 160 °C, 4 d, 82% yield).